Dampak Perubahan Iklim terhadap Lingkungan dan Tokoh-Tokoh: Dalam Novel The Great Transition (2023) Karya Nick Fuller Googins - Poppy Altrista Nadeak; Rizki Februansyah; Eni Nur Aini (Universitas Negeri Surabaya, 2026)
This research aims to analyze the impact of climate change on both the environment and the characters. It uses ecocriticism theory to examine the effects of climate change, and psychoterratic theory to analyze the psychological effects experienced by the characters in response to the climate crisis. The data sources needed were obtained from the narrative and dialogue in the novel by Nick Fuller Googins entitled The Great Transition (2023), using qualitative analysis methods. The study findings indicate that climate change leads to significant environmental changes, including air pollution from forest fires, plastic waste pollution in coastal areas, the death of wildlife due to diseases and pests, species migration, and rising sea levels caused by melting ice. Furthermore, these impacts are also directly related to the character’s life, as reflected through psychological responses such as ecological anxiety, which underscores the emotional toll of climate change on individuals. Therefore, climate change can be categorized as a major threat to environmental sustainability and human well-being.